Машина пространства - Синицын Алексей (Городская проза, 2019)
Экземпляры: Камская библиотека (20220606) / Инвентарный номер: 13851 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 38 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6